Understanding the attributes of digital wallet customers: Segmentation based on perceived risk during the Covid-19 pandemic - Sutarso, Yudi; Sekarsari, Larasati Ayu; Hidayati, Ersa Annisatul; Andariksa, Hane; Putri, Meytita Zafira (Fakultas Ekonomika dan Bisnis Universitas Kristen Satya Wacana, 2022)
This research emphasizes the importance of digital wallet customer segmentation, mainly based on customer risk perceptions during the Covid-19 pandemic. The fundamental contribution of the study was to explain the concept of perceived risk in a digital wallet, also to confirm risk factors in digital wallets, and identify segments based on perceived risk factors. The respondents are 270 digital wallet users of OVO, Gopay, and Dana obtained in Surabaya, Indonesia, during the Covid-19 pandemic, which was taken using the purposive sampling technique. The multiple analysis data were carried out using factor analysis, cluster analysis, and difference test techniques. An essential finding of this study shows that perceived risk factors consist of security, financial, social, and operational risks. There are three segments based on the perceived risk: low-risk, medium-risk, and high-risk. Each segment has different characteristics and managerial implications.